Manažerské rozhodování při řízení kvality školy. The managerial decision-making in school quality management - Voda Jan (Czech Pedagogical Society, 2012)
The paper presents some methodological applications of design-basedresearch regarding the relation between managerial decision-making and the qualityof a school. With the support of the theoretical principles of decision-making andthe concept of a good school, we review the real eff ects of our decision-makingprocesses in the phase of constituting a school and developing the school curriculum.The project is a private, bilingual primary school. The quality of the decision-makingprocesses represents the basis of the quality of the school. During a 4 year period,we were observing and evaluating how the initial decisions were reviewed and changed during the cyclical process of analysis-design-evaluation-new design. Based on our process experience, we off er some interpretations which might contribute to wider understanding of decision-making processes of the management of schools. Concurrently, we make use of the research outputs to refine a practical solution tobenefit the surveyed school.